An organic crystalline additive, its preparation method and application

CN122958290APending Publication Date: 2026-10-23TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611117074.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

很少有能够辅助钙钛矿晶体生长、钝化缺陷的同时提取并传输空穴的有机小分子添加剂,即便存在也通常是以无定形态分散于钙钛矿晶界处,难以实现空穴的高效输运,导致PSCs效率依然处于较低水平

Benefits of technology

本发明设计合成了一种新型钙钛矿太阳能电池的添加剂,利用苯并菲刚性共轭基团间的强π-π相互作用诱导有机小分子间形成紧密有序的堆叠模式,形成晶态结构,以此缩短分子间距,促进空穴在三苯胺基团间的跳跃传输,显著提升材料的空穴迁移率。同时,有机晶态添加剂中苯并菲的π电子和PbI2之间形成的π-Pb2+相互作用还能够为钙钛矿晶体提供异相成核位点,这种立方相晶态结构具有集中分布的高密度电子云特性,能够充分分散钙钛矿前驱体中的PbI2组分,辅助高质量钙钛矿晶体的形成。最终,基于此添加剂的钙钛矿太阳能电池实现了24.64%的光电转换效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958290A_ABST
    Figure CN122958290A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of perovskite solar cells, in particular to an organic crystalline additive as well as a preparation method and application thereof. The organic crystalline additive is characterized by having a structure shown in formula I: formula I. A rigid conjugated group of benzophenanthracene is used to induce a close and ordered stacking mode among organic small molecules through strong mutual interaction, so that a crystalline structure is formed, the intermolecular distance is shortened, the hopping transmission of holes among triphenylamine groups is promoted, and the hole mobility of the material is significantly improved. A perovskite solar cell based on the additive achieves a photoelectric conversion efficiency of 24.64%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite solar cell technology, and in particular to an organic crystalline additive, its preparation method, and its application. Background Technology

[0002] The carrier transport performance of perovskite solar cells (PSCs) directly determines the photoelectric conversion efficiency and stability of the corresponding devices. The carrier transport process mainly involves the perovskite light-absorbing layer, the carrier transport layer, and their interlayer interfaces in PSCs. The perovskite light-absorbing layer has the function of generating and transporting carriers, and its film quality is crucial to the efficiency of electron-hole transport and extraction. Larger grain size and dominant crystal orientation are beneficial to improving carrier concentration and transport rate, while fewer grain boundaries and defect state densities can effectively suppress nonradiative recombination of carriers. To improve the quality of the perovskite light-absorbing layer film, strategies such as composition control, solvent engineering, additive engineering, and seed-assisted growth are commonly used.

[0003] Commonly used additives in PSCs include organic / inorganic salts, small organic molecule compounds, polymers, and nanoparticles. Their mechanism of action mainly involves the interaction of special functional groups in the additives with Pb in halide perovskites. 2+ and I - Stable interactions are formed to aid the growth of perovskite crystals or passivate defects on the surface of perovskite crystals, thereby improving the carrier transport efficiency of perovskite polycrystalline thin films. Organic small molecule compounds are widely used in various high-efficiency and stable PSC devices due to their advantages such as simple synthesis and separation, flexible and tunable functional groups, and excellent solution processing properties.

[0004] Currently, commonly used small organic molecule compounds are relatively large in size, and their main functional groups are Lewis acid and Lewis base functional groups, which interact with Pb. 2+ or I - Coordination effects facilitate perovskite crystal growth and distribution at grain boundaries in perovskite films, passivating defects. Few small organic molecule additives can simultaneously aid perovskite crystal growth, passivate defects, and extract and transport holes. Even when present, they are usually amorphously dispersed at grain boundaries, hindering efficient hole transport and resulting in low PSC efficiency. Commonly used randomly dispersed small organic molecule additives also have limited effects on promoting perovskite crystal nucleation and growth, failing to significantly improve carrier transport performance in perovskite films. Summary of the Invention

[0005] The purpose of this invention is to provide an organic crystalline additive, its preparation method, and its application, in order to solve the problems existing in the prior art.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: One of the technical solutions of this invention provides an organic crystalline additive having the structure shown in Formula I: Formula I.

[0007] The second technical solution of the present invention provides a method for preparing the above-mentioned organic crystalline additive, comprising the following steps: Under an inert atmosphere, 2-bromotriphenylene, potassium carbonate, 4-boronate-4',4''-dimethoxytriphenylamine and solvent are mixed, and then tetra(triphenylphosphine)palladium is added to react and obtain an organic crystalline additive.

[0008] The third technical solution of the present invention provides a perovskite solar cell, comprising: a substrate and an electron transport layer, a perovskite thin film layer, a hole transport layer and a top electrode stacked on the substrate; The perovskite thin film layer contains the aforementioned organic crystalline additives.

[0009] The fourth technical solution of this invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: 1) Select a conductive glass substrate; 2) An electron transport layer is fabricated on a conductive glass substrate; 3) Prepare a perovskite thin film containing organic crystalline additives on the electron transport layer; 4) Fabricate a hole transport layer on a perovskite thin film; 5) Deposit the top electrode on the hole transport layer to obtain a perovskite solar cell.

[0010] Optionally, the method for preparing the perovskite thin film layer in step 3) includes: S1. A perovskite solution is obtained by mixing lead iodide, formamidinium hydroiodate, methyl ammonium bromide, cesium iodide, and a solvent; S2. After spin-coating the perovskite solution onto the electron transport layer, a mixed solution of the organic crystalline additive and solvent described in claim 1 is added dropwise, and then annealed under an inert atmosphere to obtain a perovskite thin film layer.

[0011] Compared with the prior art, the present invention has the following beneficial effects: This invention designs and synthesizes a novel additive for perovskite solar cells. It utilizes the strong π-π interactions between rigid conjugated groups of benzo[a]phenanthrene to induce a tightly ordered stacking pattern between small organic molecules, forming a crystalline structure. This shortens the intermolecular distance, promotes hole hopping between triphenylamine groups, and significantly improves the hole mobility of the material. Simultaneously, the π-Pb electrons formed between the π electrons of benzo[a]phenanthrene and PbI2 in the organic crystalline additive...2+ The interaction also provides heterogeneous nucleation sites for the perovskite crystal. This cubic crystalline structure has a concentrated, high-density electron cloud, which can effectively disperse the PbI2 component in the perovskite precursor, thus aiding in the formation of high-quality perovskite crystals. Ultimately, the perovskite solar cell based on this additive achieved a photoelectric conversion efficiency of 24.64%. Attached Figure Description

[0012] Figure 1 The XRD pattern of the organic crystalline additive T-TPA; Figure 2 TEM image and electron diffraction pattern of the organic crystalline additive T-TPA; Figure 3 JV curves before and after adding T-TPA to PSCs. Detailed Implementation

[0013] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0014] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0015] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0016] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0017] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0018] All raw materials used in this invention can be obtained commercially or prepared using existing technologies.

[0019] This invention provides an organic crystalline additive having the structure shown in Formula I: Formula I.

[0020] The present invention also provides a method for preparing the above-mentioned organic crystalline additive, comprising the following steps: Under an inert atmosphere, 2-bromotriphenylene, potassium carbonate, 4-boronate-4',4''-dimethoxytriphenylamine and solvent were mixed, and then tetra(triphenylphosphine)palladium was added to carry out reaction 2 to obtain an organic crystalline additive.

[0021] In a preferred embodiment of the present invention, 2-bromotriphenylene, potassium carbonate and 4-boronate-4',4''-dimethoxytriphenylamine are added to a solvent, and the system is mixed and dissolved uniformly by magnetic stirring. Then tetra(triphenylphosphine)palladium is added and the mixture is heated to reflux to carry out the reaction.

[0022] In this invention, the molar ratio of 2-bromotriphenylene to 4-boronate-4',4''-dimethoxytriphenylamine is 1:1; the molar ratio of potassium carbonate to tetra(triphenylphosphine)palladium is 10:1; the molar ratio of 2-bromotriphenylene to potassium carbonate is 1:2; the solvent is a mixture of tetrahydrofuran (THF) and water; the volume ratio of tetrahydrofuran to water is 4:1; and the inert atmosphere is preferably argon.

[0023] In a preferred embodiment of the present invention, after the reaction 2 is completed, a post-processing is required. The post-processing includes: placing the product obtained from the reaction in ice water, and then sequentially performing extraction, filtration, vacuum distillation, and column chromatography to obtain an organic crystalline additive. The extractant used in the extraction is dichloromethane; the chromatographic column is a SiO2 column.

[0024] In this invention, the temperature of reaction 2 is 70°C and the time is 36 hours.

[0025] In this invention, the synthetic route for the organic crystalline additive is as follows: .

[0026] In this invention, the preparation method of the 4-boronate ester-4',4''-dimethoxytriphenylamine includes the following steps: Under an inert atmosphere, 4-bromo-N,N'-bis(4-methoxyphenyl)aniline, potassium acetate, and a solvent were mixed, and then pinacol diborate and palladium bis(triphenylphosphine) dichloride were added to carry out reaction 1 to obtain 4-boronate 4',4''-dimethoxytriphenylamine.

[0027] In a preferred embodiment of the present invention, after reaction 1 is completed, post-processing is required; the post-processing includes: placing the product in ice water, and sequentially performing extraction filtration, vacuum distillation and column chromatography to obtain 4-boronate-4',4''-dimethoxytriphenylamine. The extractant used in the extraction filtration is dichloromethane; the chromatographic column is a SiO2 column.

[0028] In a preferred embodiment of the present invention, under an inert atmosphere, a mixture of 4-bromo-N,N'-bis(4-methoxyphenyl)aniline and potassium acetate is dissolved in a solvent, and then stirred at room temperature for 30 min. Pinacol diborate and bis(triphenylphosphine)palladium dichloride are then added to the reaction system to carry out reaction 1.

[0029] In this invention, the molar ratio of 4-bromo-N,N'-bis(4-methoxyphenyl)aniline to pinacol borate is 1:2; the molar ratio of potassium acetate to bis(triphenylphosphine)palladium dichloride is 76:1; the molar ratio of 4-bromo-N,N'-bis(4-methoxyphenyl)aniline to potassium acetate is 1:3.8; the solvent is N,N-dimethylformamide (DMF); the volume ratio of potassium acetate to solvent is 3.8 mol:10 mL; and the inert atmosphere is preferably argon.

[0030] In this invention, the temperature of reaction 1 is 80°C and the time is 12 hours.

[0031] In this invention, the synthetic route for 4-boronate ester-4',4''-dimethoxytriphenylamine is as follows: .

[0032] The present invention also provides a perovskite solar cell, comprising: a substrate and an electron transport layer, a perovskite thin film layer, a hole transport layer and a top electrode stacked on the substrate; The perovskite thin film layer contains the aforementioned organic crystalline additives.

[0033] In this invention, the substrate is fluorine-doped tin oxide conductive glass; the electron transport layer is a dense titanium dioxide layer and mesoporous titanium dioxide; the hole transport layer is an HTM thin film; and the top electrode is gold.

[0034] This invention also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: 1) Select a conductive glass substrate; 2) An electron transport layer is fabricated on a conductive glass substrate; 3) Prepare a perovskite thin film containing organic crystalline additives on the electron transport layer; 4) Fabricate a hole transport layer on a perovskite thin film; 5) Deposit the top electrode on the hole transport layer to obtain a perovskite solar cell.

[0035] Step 1) of the present invention involves cleaning and oxygen plasma treatment of the conductive glass layer to obtain a treated conductive glass layer substrate. In this invention, the cleaning process involves sequentially applying water, acetone, isopropanol, and ethanol to the conductive glass using ultrasonic treatment; the oxygen plasma treatment is performed at an intensity of 80W for 10 minutes.

[0036] Step 2) of this invention involves depositing a titanium source solution onto a conductive glass substrate to form a dense titanium dioxide layer; then spin-coating a titanium dioxide particle slurry onto the conductive glass substrate and performing a first sintering to obtain a mesoporous titanium dioxide layer; then subjecting the surface of the mesoporous titanium dioxide layer to oxygen plasma treatment; finally, spin-coating a lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) solution onto the surface of the mesoporous titanium dioxide layer and performing a second sintering to remove moisture to obtain an electron transport layer.

[0037] In this invention, the titanium source solution is composed of bis(acetylacetonyl)diisopropyl titanate solution, acetylacetone, and anhydrous isopropanol; the concentration of the bis(acetylacetonyl)diisopropyl titanate solution is 75 wt.%; the solvent of the bis(acetylacetonyl)diisopropyl titanate solution is isopropanol; the volume ratio of the bis(acetylacetonyl)diisopropyl titanate solution to acetylacetone is 3:2; and the volume ratio of acetylacetone to anhydrous isopropanol is 1:25.

[0038] In this invention, the titanium source solution is deposited on a conductive glass substrate by spray thermal pyrolysis; the deposition temperature is 450°C and the carrier gas is oxygen.

[0039] In this invention, the titanium dioxide particle slurry is diluted in ethanol; the mass ratio of titanium dioxide particle slurry to ethanol is 1:6; and the particle size of the titanium dioxide particles is 30 nm.

[0040] In this invention, the spin coating speed of the titanium dioxide particle slurry is 4000 rpm and the time is 20 s; the temperature of the first sintering is 500℃ and the time is 30 min.

[0041] In this invention, the oxygen plasma treatment of the mesoporous titanium dioxide layer surface is performed with a power of 80W for 15 minutes.

[0042] In this invention, the concentration of the Li-TFSI solution is 1 mg / mL; the Li-TFSI solution is spin-coated onto the surface of the mesoporous titanium dioxide layer at a rotation speed of 4000 rpm for 30 s; and the secondary sintering temperature is 500 °C for 30 min.

[0043] In this invention, the method for preparing the perovskite thin film layer in step 3) includes: S1. A perovskite solution is obtained by mixing lead iodide, formamidinium hydroiodate, methyl ammonium bromide, cesium iodide, and a solvent; S2. After spin-coating the perovskite solution onto the electron transport layer, a mixed solution of the organic crystalline additive and solvent described in claim 1 is added dropwise, and then annealed under an inert atmosphere to obtain a perovskite thin film layer.

[0044] In this invention, the perovskite solution contains lead iodide at a concentration of 1.65 mol / L, formamidinium hydroiodate at a concentration of 1.31 mol / L, methylammonium bromide at a concentration of 0.15 mol / L, and cesium iodide at a concentration of 0.08 mol / L. The mixing temperature in step S1 is 70℃ and the time is 15 minutes.

[0045] In this invention, spin coating is a two-step process to spin-coat the perovskite precursor solution onto the substrate. The first spin coating is performed at 1000 rpm for 10 seconds, and the second spin coating is performed at 6000 rpm for 20 seconds, for a total of 30 seconds. At the 25th second, a mixed solution of organic crystalline additive and solvent is added dropwise.

[0046] In this invention, the concentration of the mixed solution of the organic crystalline additive and the solvent is 1 mmol / L; the solvent is a chlorobenzene solution; and the volume ratio of the perovskite solution to the mixed solution is 10:1. In step S2, the annealing temperature is 120℃ and the time is 20min.

[0047] In this invention, the inert atmosphere in step S2 is preferably argon.

[0048] In a preferred embodiment of the present invention, after the perovskite thin film layer is cooled, 100 µl of isopropanol is dropped onto it by spin coating at a speed of 3500 rpm to remove excess perovskite precursor.

[0049] Step 4 of this invention involves mixing HTM solution, Li-TFSI solution and 4-tert-butylpyridine (TBP) to obtain a mixed solution, spin-coating the mixed solution onto a perovskite thin film layer, and drying it to obtain a hole transport layer.

[0050] In this invention, the HTM solution is prepared by dissolving 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (spirocyclic OMeTAD) in chlorobenzene; the ratio of spirocyclic OMeTAD to chlorobenzene is 72.3 mg: 1 mL.

[0051] In this invention, the Li-TFSI solution is prepared from Li-TFSI and acetonitrile; the concentration of the Li-TFSI solution is 520 mg / L.

[0052] In this invention, the volume ratio of HTM solution, Li-TFSI solution and TBP is 1000 : 17.5 : 28.8.

[0053] In this invention, the spin coating speed of the mixed solution onto the perovskite thin film layer is 4000 rpm, and the homogenization time is 20 s.

[0054] In this invention, drying involves placing the sample in a desiccator for 24 hours.

[0055] Step 5 of this invention involves depositing the top electrode on the hole transport layer to complete the fabrication of the perovskite solar cell.

[0056] In this invention, the top electrode is gold; the thickness of the top electrode is 100 nm, and the deposition rate is 1 Å s. -1 .

[0057] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0058] Example 1 (1) Synthesis of 4-boronate-4',4''-dimethoxytriphenylamine Under an argon atmosphere, a mixture of 1 mol 4-bromo-N,N'-bis(4-methoxyphenyl)aniline and 3.8 mol potassium acetate was dissolved in a flask containing 10 mL DMF, and the mixture was stirred at room temperature for 30 min. 2 mol pinacol diborate and 0.05 mol bis(triphenylphosphine)palladium dichloride were added to the mixture, and the temperature was raised to 80 °C, and the reaction was allowed to proceed for 12 h. The reaction product was poured into ice water, extracted with dichloromethane, filtered, distilled under reduced pressure, and separated by SiO2 column chromatography to obtain a white solid, namely 4-boronate-4',4''-dimethoxytriphenylamine.

[0059] (2) Synthesis of 4-(triphenyl-2-yl)-4',4''-dimethoxytriphenylamine (T-TPA) Under an argon atmosphere, 1 mol of 2-bromotriphenylene, 2 mol of potassium carbonate, and 1 mol of 4-boronate-4',4''-dimethoxytriphenylamine were added to a mixed solvent of 10 mL of tetrahydrofuran (THF) and 2.5 mL of H2O. The mixture was stirred magnetically until homogeneous. Then, 0.2 mol of tetra(triphenylphosphine)palladium was added, and the mixture was heated to 70 °C and refluxed for 36 h. After the reaction was completed, the product was poured into ice water, extracted with dichloromethane, filtered, distilled under reduced pressure, and separated by SiO2 column chromatography to obtain solid T-TPA.

[0060] The T-TPA proton NMR spectrum data are shown below: 1 H-NMR (400 MHz, CDCl3) δ = 8.65–8.57 (m, 2H), 8.50 (dd, J = 7.8, 1.8 Hz, 1H), 8.43 (d, J = 9.0 Hz, 1H), 8.27 (dd, J = 8.3, 1.4 Hz, 1H), 8.18 (d, J = 2.4 Hz,1H), 7.65–7.50 (m, 2H), 7.29 (dd, J = 8.9, 2.3 Hz, 1H), 7.19 (d, J = 8.9 Hz, 3H), 6.90 (d, J = 8.9 Hz, 3H), 3.84 (s, 6H) ppm. The XRD pattern of the organic crystalline additive T-TPA is as follows: Figure 1 As shown, by Figure 1 It can be seen that T-TPA molecules form a crystalline structure after being stacked in an orderly manner. Crystalline T-TPA has a cubic phase orientation, and its specific molecular arrangement orientation can be determined by... Figure 2 The TEM spectrum and its electron diffraction information were obtained.

[0061] Example 2 PSCs were fabricated using a device structure of FTO / cTiO2 / mTiO2 / Perovskite / Spiro OMeTAD / Au. (1) FTO glass pretreatment: FTO glass was cleaned by ultrasonic treatment with deionized water, acetone, isopropanol and ethanol in sequence; then, FTO substrate was treated with 80 W oxygen plasma for 10 minutes.

[0062] (2) Preparation of c-TiO2 layer: At 470℃, 600µl of bis(acetylacetonyl)diisopropyl titanate (75wt.% in isopropanol) and 400µl of acetylacetone were dispersed in 10 ml of anhydrous isopropanol to obtain a mixed solution; the mixed solution was deposited on the FTO substrate by spray thermal pyrolysis to form a 10 nm TiO2 dense layer (c-TiO2 layer), wherein the deposition temperature was 450℃ and the carrier gas was O2.

[0063] (3) Preparation of m-TiO2 layer: A slurry of TiO2 particles with a particle size of 30 nm diluted in ethanol (mass ratio of ethanol to TiO2 particles slurry of 1:6) was spin-coated onto the c-TiO2 layer at a speed of 4000 rpm for 20 seconds. The layer was then sintered at 500℃ for 30 minutes to prepare a 30 nm mesoporous TiO2 (m-TiO2) layer; The m-TiO2 layer was treated with 80 W oxygen plasma for 15 minutes; then, a 1 mg / mL Li-TFSI solution (deionized water as solvent) was spin-coated onto the m-TiO2 at 4000 rpm for 30 seconds, and sintered at 500 °C for 30 minutes to remove moisture.

[0064] (4) Preparation of perovskite thin film: A mixture of 1.60 M PbI2, 1.31 M FAI, 0.15 M MABr, and 0.08 M CsI with 0.05 M excess PbI2 was dissolved in 1 mL of a mixed solution of DMF and DMSO (4 / 1, v / v), and stirred at 70 °C for 15 minutes to prepare the CsI thin film. 0.05 FA 0.85 MA 0.10 Pb(I 0.97 Br 0.03 )3 Perovskite solution; The perovskite solution prepared above was spin-coated onto the m-TiO2 layer at 1000 rpm for 10 s, and then spin-coated onto the m-TiO2 layer at 6000 rpm for 20 s, for a total spin-coating time of 30 s. At the 25th second, 100 µL of a 1 mM T-TPA solution (chlorobenzene solution as solvent) was rapidly dropped onto the spin-coated m-TiO2 layer. Afterward, the perovskite film was annealed at 120 °C for 20 minutes under an argon atmosphere. After the perovskite cooled, 100 µL of isopropanol was dropped onto the film by spin-coating at 3500 rpm / min to remove excess perovskite precursor, thus obtaining the perovskite film layer.

[0065] (5) Preparation of HTM thin film layer (Spiro OMeTAD): 72.3 mg of spirocyclic OMeTAD and 1 mL of chlorobenzene were mixed to obtain HTM solution; 17.5 µl of 520 mg / ml Li-TFSI solution (solvent: acetonitrile) and 28.8 µl of TBP dopant were added to the HTM solution. After mixing thoroughly, the resulting solution was spin-coated onto the surface of the perovskite thin film at 4000 rpm for 20 s. After spin coating, the film was placed in a desiccator for 24 hours to obtain the HTM thin film.

[0066] (6) Fabrication of the top electrode: A 100 nm gold top electrode was fabricated under high vacuum at a speed of 1 Å s. -1 The perovskite solar cells (PSCs) are obtained by depositing the HTM thin film at a certain rate.

[0067] Comparative Example 1 The only difference from Example 2 is that in step (4), 100µL of 1 mM T-TPA solution is replaced with 100µL of chlorobenzene. All other steps and process parameters are completely consistent with Example 2.

[0068] Test case The performance of the perovskite solar cells prepared in Example 2 and Comparative Example 1 was tested. The test method was to obtain the corresponding photovoltaic performance parameters by testing the JV curves of the two samples under standard sunlight and comparing their photoelectric conversion efficiency. The test results are shown in Table 1 and 2. Figure 3 As shown in Table 1 and Figure 3 It can be seen that the photoelectric conversion efficiency of the device with added T-TPA (Example 2) is 24.64%, while the photoelectric conversion efficiency of the device in Comparative Example 1 without added T-TPA is only 22.36%. The test results show that T-TPA can effectively improve the hole transport efficiency of the perovskite grain boundaries and its interface with the hole transport layer, passivate the surface defects of the perovskite grains, suppress the nonradiative recombination of charge carriers, and significantly improve the efficiency of PSCs devices.

[0069] Table 1. Photovoltaic parameters of PSCs devices

[0070] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An organic crystalline additive, characterized in that, It has the structure shown in Equation I: Formula I.

2. A method for preparing the organic crystalline additive according to claim 1, characterized in that, Includes the following steps: Under an inert atmosphere, 2-bromotriphenylene, potassium carbonate, 4-boronate-4',4''-dimethoxytriphenylamine and solvent are mixed, and then tetra(triphenylphosphine)palladium is added to react and obtain an organic crystalline additive.

3. The preparation method according to claim 2, characterized in that, The molar ratio of 2-bromotriphenylene to 4-boronate-4',4''-dimethoxytriphenylamine is 1:1; the molar ratio of potassium carbonate to tetrakis(triphenylphosphine)palladium is 10:1; and the molar ratio of 2-bromotriphenylene to potassium carbonate is 1:

2.

4. The preparation method according to claim 2, characterized in that, The reaction was carried out at a temperature of 70°C for 36 hours.

5. A perovskite solar cell, characterized in that, include: A substrate and an electron transport layer, a perovskite thin film layer, a hole transport layer and a top electrode stacked on the substrate; The perovskite thin film layer contains the organic crystalline additive as described in claim 1.

6. The perovskite solar cell according to claim 5, characterized in that, The substrate is fluorine-doped tin oxide conductive glass; the electron transport layer is a dense titanium dioxide layer and mesoporous titanium dioxide; the hole transport layer is an HTM thin film; and the top electrode is gold.

7. A method for preparing a perovskite solar cell according to any one of claims 5 to 6, characterized in that, Includes the following steps: 1) Select a conductive glass substrate; 2) An electron transport layer is fabricated on a conductive glass substrate; 3) Prepare a perovskite thin film containing organic crystalline additives on the electron transport layer; 4) Fabricate a hole transport layer on a perovskite thin film; 5) Deposit the top electrode on the hole transport layer to obtain a perovskite solar cell.

8. The preparation method according to claim 7, characterized in that, Step 3) involves the following methods for preparing the perovskite thin film layer: S1. A perovskite solution is obtained by mixing lead iodide, formamidinium hydroiodate, methyl ammonium bromide, cesium iodide, and a solvent; S2. After spin-coating the perovskite solution onto the electron transport layer, a mixed solution of the organic crystalline additive and solvent described in claim 1 is added dropwise, and then annealed under an inert atmosphere to obtain a perovskite thin film layer.

9. The preparation method according to claim 8, characterized in that, In the perovskite solution, the concentration of lead iodide is 1.65 mol / L, the concentration of formamidinium hydroiodate is 1.31 mol / L, the concentration of methylammonium bromide is 0.15 mol / L, and the concentration of cesium iodide is 0.08 mol / L. The mixing temperature in step S1 is 70°C, and the time is 15 minutes.

10. The preparation method according to claim 8, characterized in that, The concentration of the mixed solution of the organic crystalline additive and the solvent is 1 mmol / L; the solvent is a chlorobenzene solution; the volume ratio of the perovskite solution to the mixed solution is 10:

1. In step S2, the annealing temperature is 120℃ and the time is 20min.